Social Health as a Means of Defining Personality’s Life Orientations - Tomchuk, B. P. (Psychological Prospects Journal, 2012)
The relationships between social health and personality’s life orientations on the basis of generalization of theoretical and empirical researches are analyzed. Special attention is paid to the role of factors which appear as social health determinants. The process of life values mastering and their transformation into substantial elements of personality’s value conceptions are characterized. Life orientations influence upon social life quality is highlighted. Peculiarities of forming of personality’s value orientations are described.
Keywords: social health, life orientations